Electrochemical pretreatment of waste NCM523 cathode material and subsequent recovery method of polycrystalline to single crystal

CN122931119APending Publication Date: 2026-10-16TONGREN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610974329.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0007]针对上述现有退役NCM523正极材料回收方法存在晶体结构易受破坏、表面杂质难以彻底去除、能耗高且操作复杂以及再生效果不可控等问题,导致再生材料循环性能下降、电化学活性不足,本发明提供废旧NCM523正极材料电化学预处理及后续多晶转变单晶的回收方法,在保持晶体结构稳定性前提下,实现高效清洗、精准剥离和可控再生,显著提升再生材料循环性能和倍率性能的技术效果

Benefits of technology

1、本发明的方法采用电解预嵌锂处理和低压脉冲剥离,能够在控制电位和处理时间的条件下进行,以保证正极材料晶体结构稳定,并实现表面残留物的彻底去除以及预嵌锂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931119A_ABST
    Figure CN122931119A_ABST
Patent Text Reader

Abstract

The application discloses a recycling method for waste NCM523 positive electrode material electrochemical pretreatment and subsequent polycrystal conversion monocrystal, and steps are as follows: S1, pretreatment: the disassembled retired NCM523 positive electrode material is sequentially subjected to vacuum drying, solvent immersion washing, and vacuum drying again for pretreatment; S2, electrolytic pre-lithium intercalation treatment: the pretreated NCM523 positive electrode material is subjected to constant-potential electrochemical pre-lithium intercalation treatment in a three-electrode electrochemical system; S3, stripping: the NCM523 positive electrode material after electrolytic pre-lithium intercalation is subjected to low-pressure pulse stripping to obtain stripped active material; and S4, high-temperature sintering: the stripped active material is ground, mixed with a lithium source molten salt, and subjected to high-temperature sintering by subsection heating. The recycling method realizes efficient cleaning, accurate stripping and controllable regeneration under the premise of maintaining the stability of the crystal structure, and significantly improves the cycle performance and rate performance of the regenerated material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for the electrochemical pretreatment of waste NCM523 cathode material and subsequent polycrystalline to single-crystal recycling, belonging to the field of ternary lithium battery recycling technology. Background Technology

[0002] With the accelerating global energy structure transformation, the development and utilization of clean and renewable energy have received increasing attention. Renewable energy sources such as solar and wind power are intermittent and unstable, requiring efficient energy storage technologies to ensure stable output and large-scale application. Lithium-ion batteries, due to their high energy density, long cycle life, and relatively high safety, have become an important component of energy storage and power systems.

[0003] In the field of power batteries, NCM (nickel-cobalt-manganese ternary) materials have become the mainstream cathode materials due to their high capacity, low cost, high energy density, and good cycle performance. Among them, NCM523 material balances nickel content and structural stability, and has advantages in both energy density and safety, making it widely used in new energy vehicles and energy storage systems. However, with the increasing number of scrapped batteries, the recycling and regeneration of retired power batteries has become a critical issue that urgently needs to be addressed in the new energy industry chain.

[0004] Currently, the recycling technologies for retired NCM523 cathode materials mainly include physical crushing, wet chemical leaching, and electrochemical stripping. Physical methods: Cathode materials are recovered through crushing and sieving, but this easily damages the crystal structure, leading to a decrease in the electrochemical performance of the recycled material. Wet chemical leaching: Metals are extracted using acids or alkalis; although resources such as nickel, cobalt, and lithium can be recovered, it is energy-intensive, complex to operate, and causes environmental pollution. Electrochemical recycling: Metals are recovered through electrochemical reduction or stripping, but the protection of the material's crystal structure is limited, and the removal of surface impurities from retired NCM523 is incomplete, making it difficult to guarantee cycle performance.

[0005] After dismantling, retired NCM523 cathode materials typically contain residual electrolyte, conductive agents, and coating agents, among other surface impurities. These impurities not only affect the electrochemical performance of the material but also lead to structural instability and reduced activity during subsequent regeneration. Traditional high-temperature sintering, liquid-phase impregnation, or physical coating methods have the following drawbacks: 1) High-temperature sintering easily causes irreversible lattice deformation, resulting in decreased cycle performance; 2) Liquid-phase coating or impregnation methods are energy-intensive, complex to operate, and cannot uniformly remove surface impurities; 3) Multi-step processing increases costs and operational difficulty, reducing the economic viability and sustainability of material regeneration.

[0006] Therefore, there is an urgent need for a new process that can protect the crystal structure, remove surface residual impurities, precisely peel off, and achieve regenerated sintering of single-crystal NCM523 cathode materials. Based on the above technical background, this invention proposes an electrochemical pretreatment method for waste NCM523 cathode materials and subsequent polycrystalline to single-crystal recycling method. This method integrates dismantling, vacuum drying, solvent cleaning, electrochemical peeling, and polycrystalline sintering into a single process for regenerating decommissioned NCM523, significantly improving the cycle stability, electrochemical performance, and energy storage efficiency of the recycled materials, while reducing energy consumption and environmental impact. It has broad application prospects and industrialization value. Summary of the Invention

[0007] To address the problems of existing methods for recycling retired NCM523 cathode materials, such as easy damage to the crystal structure, difficulty in completely removing surface impurities, high energy consumption, complex operation, and uncontrollable regeneration effect, which lead to decreased cycle performance and insufficient electrochemical activity of the recycled materials, this invention provides an electrochemical pretreatment and subsequent polycrystalline to single-crystal recycling method for waste NCM523 cathode materials. While maintaining the stability of the crystal structure, this method achieves efficient cleaning, precise stripping, and controllable regeneration, significantly improving the cycle performance and rate performance of the recycled materials.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: an electrochemical pretreatment method for waste NCM523 cathode material and a subsequent polycrystalline to single-crystal recycling method, the specific recycling steps of which are as follows: S1. Pretreatment: The disassembled retired NCM523 cathode material is pretreated by vacuum drying, solvent washing and vacuum drying again to obtain pretreated NCM523 cathode material. S2. Electrolytic pre-lithiation treatment: The pretreated NCM523 cathode material is subjected to constant potential electrochemical pre-lithiation treatment in a three-electrode electrochemical system to obtain the electrolytically pre-lithiation-treated NCM523 cathode material. S3. Stripping: The active material of the pre-lithiated NCM523 cathode material after electrolysis is separated from the current collector by a low-voltage pulse stripping method, and then cleaned and dried to obtain the stripped active material, i.e., the stripped NCM523 cathode material. S4. High-temperature sintering: The stripped active material is ground into powder, then mixed evenly with lithium source molten salt through grinding, and then sintered at high temperature using a segmented heating method. After sintering, it is naturally cooled to room temperature, then subjected to ultrasonic treatment, centrifugal separation, cleaning, and vacuum drying to obtain single-crystal NCM523 cathode material.

[0009] Preferably, in step S1, in the three-electrode electrochemical system, the reference electrode is a silver chloride electrode, the counter electrode is a platinum electrode, the working electrode is a pretreated NCM523 positive electrode material, and the electrolyte is a lithium sulfate solution.

[0010] Preferably, the concentration of the lithium sulfate solution is 1~2 mol / L.

[0011] Preferably, the concentration of the lithium sulfate solution is 2 mol / L.

[0012] Preferably, in step S1, the conditions for the constant potential electrochemical pre-lithiation treatment are: electrolysis potential of -1.2 to -1.4V and electrolysis time of 1 to 3h.

[0013] Preferably, the conditions for the constant potential electrochemical pre-lithiation treatment are: electrolysis potential of -1.3~1.35V and electrolysis time of 1~3h.

[0014] Preferably, in step S2, the conditions for the low-voltage pulse stripping method are: voltage of 15~25V, power-on time of 1~3s, power-off time of 3~5s, and 1~3 cycles.

[0015] Preferably, the low-voltage pulse stripping method employs a dual-electrode system, with the positive electrode being the pre-lithiated NCM523 positive electrode material and the negative electrode being a platinum electrode, and the electrolyte being a lithium sulfate solution.

[0016] Preferably, the conditions for the low-voltage pulse stripping method are: voltage of 20V, power-on time of 2s, power-off time of 4s, and two cycles.

[0017] Preferably, in step S3, the lithium source molten salt is composed of lithium nitrate, lithium hydroxide monohydrate, and lithium carbonate.

[0018] Preferably, in step S3, the lithium source molten salt is added with an excess coefficient of 5-15%.

[0019] Preferably, the lithium source molten salt is added in excess at a rate of 10%.

[0020] Preferably, the mass ratio of lithium nitrate, lithium hydroxide monohydrate and lithium carbonate is 3:2:(0.3~1).

[0021] Preferably, in step S3, the high-temperature sintering is carried out in a segmented heating manner as follows: under an oxygen atmosphere, the temperature is first held at 300℃ for 1.5~2.5h, then held at 600℃ for 3.5~4.5h, and finally held at 900~970℃ for 10~18h.

[0022] Preferably, under an oxygen atmosphere, the temperature is first kept at 300℃ for 1.5~2.5h, then at 600℃ for 3.5~4.5h, and finally at 900~970℃ for 10~18h.

[0023] Preferably, in step S1, the solvent is dimethyl carbonate and an alcohol solvent.

[0024] Preferably, the alcohol solvent is one of methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, isobutanol, sec-butanol, tert-butanol, n-pentanol, sec-pentanol, n-octanol, or sec-octanol.

[0025] Preferably, the vacuum drying conditions are: temperature 80~100℃, time 6~12h.

[0026] Preferably, the disassembled retired NCM523 cathode material is obtained by discharging a used NCM523 pouch battery to 1.1V, repeating the discharge 3-4 times to ensure voltage stability after discharge, and then disassembling the battery in a fume hood. In another embodiment, the present invention provides a single-crystal NCM523 cathode material obtained by the above-described recycling method.

[0027] In another embodiment, the present invention provides a lithium-ion battery comprising recycled single-crystal NCM523 cathode material obtained by the above-described recycling method.

[0028] The aforementioned lithium-ion batteries are used in new energy vehicles, energy storage systems, or portable electronic devices.

[0029] Compared with the prior art, the present invention has the following beneficial effects: 1. The method of the present invention employs electrolytic pre-lithiation treatment and low-voltage pulse stripping, which can be carried out under controlled potential and processing time conditions to ensure the stability of the positive electrode material crystal structure and achieve complete removal of surface residues and pre-lithiation.

[0030] 2. High-efficiency stripping: The method of this invention uses pulse voltage to achieve high-efficiency stripping of current collectors and active materials on the surface of decommissioned NCM523 cathode materials in a short time, thereby improving processing efficiency.

[0031] 3. Material structure protection: The peeling process of this invention is gentle and does not damage the crystal structure of the cathode material, which helps to maintain the cycle performance and rate performance of the recycled material.

[0032] 4. Reduced energy consumption and easy operation: This invention uses low-voltage pulse voltage and simple two electrodes, eliminating the need for high temperature or complex chemical treatment, thus saving energy and making operation simple.

[0033] 5. Improved material regeneration performance: The present invention reduces the residue on the surface of the material after stripping, which is beneficial for subsequent sintering with molten salt, lithium hydroxide or lithium carbonate to prepare single crystal NCM523, thereby improving the electrochemical activity and cycle stability of the regenerated material.

[0034] 6. Wide range of applications: The method of this invention can flexibly adjust the pulse voltage parameters and processing time, and is applicable to retired NCM523 cathode materials of different specifications and conditions, and has high practicality and promotion value. Attached Figure Description

[0035] Figure 1 XRD patterns of different potentials under 1h electrolysis time provided in Examples 1-5 of the present invention; Figure 2 XRD patterns of different potentials under 2h electrolysis time provided in Examples 1-5 of the present invention; Figure 3 XRD patterns of different potentials under 3h electrolysis time provided in Examples 1-5 of the present invention; Figure 4 The XRD pattern of the waste NCM523 cathode material of this invention; Figure 5 XRD patterns of low-voltage pulse stripping provided in Embodiment 1 of the present invention and XRD patterns of conventional mechanical stripping in Comparative Example 1; Figure 6 This is a stripping image after low-voltage pulse stripping provided in Embodiment 1 of the present invention; Figure 7 The XRD pattern of the single-crystal NCM523 cathode material provided in Embodiment 1 of the present invention; Figure 8 A comparison chart of the cycle performance of single-crystal NCM523 cathode material and waste NCM523 cathode material provided in Embodiment 1 of the present invention; Figure 9 A comparison chart of the rate performance of single-crystal NCM523 cathode material and waste NCM523 cathode material provided in Embodiment 1 of the present invention; Figure 10 The image shows the SEM image of the waste NCM523 cathode material of this invention. Figure 11 SEM image of the single-crystal NCM523 cathode material provided in Example 2 of the present invention. Detailed Implementation

[0036] The following is a clear and complete description of the technical solutions in the implementation of the present invention. The described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0037] The first aspect of this invention provides a method for electrochemical pretreatment of waste NCM523 cathode material and subsequent polycrystalline transformation to single crystal recycling, comprising the following steps: S1. Preprocessing: S1.1 Dry the disassembled retired NCM523 cathode material in a vacuum environment at a temperature of 80~100℃ for 6~12 hours to remove residual moisture from the surface and inside of the material; S1.2. The dried NCM523 cathode material is then rinsed with solvent and dried again in a vacuum environment at a temperature of 80~100℃ for 6~12h to obtain the pretreated NCM523 cathode material. The solvent is dimethyl carbonate (DMC) and alcohol solvents; S2. Electrolytic pre-lithiation treatment: The pretreated NCM523 cathode material is subjected to constant potential electrochemical pre-lithiation treatment in a three-electrode electrochemical system. In the three-electrode electrochemical system: the reference electrode is a silver chloride electrode, the counter electrode is a platinum electrode, the working electrode is the pretreated NCM523 cathode material, the electrolyte is a lithium sulfate solution, the electrolysis potential is -1.2~-1.4V, and the electrolysis time is 1~3h, to obtain the NCM523 cathode material after electrolytic pre-lithiation. S3. Stripping: The active material of the pre-lithiated NCM523 cathode material after electrolysis is separated from the current collector using a low-voltage pulse stripping method. A dual-electrode system is used: the positive electrode is the pre-lithiated NCM523 cathode material after electrolysis, and the negative electrode is a platinum electrode. The electrolyte is a lithium sulfate solution. The conditions for the low-voltage pulse stripping method are: voltage 15~25V, energizing time 1~3s, de-energizing time 3~5s, 1~3 cycles, and drying in a vacuum environment at a temperature of 80~100℃ for 6~12h to obtain the stripped active material, i.e., the stripped NCM523 cathode material. S4, High-temperature sintering: S4.1 Grind the stripped active material into powder, and then mix it evenly with the lithium source molten salt by grinding. The lithium source molten salt is composed of lithium nitrate, lithium hydroxide monohydrate and lithium carbonate to obtain a mixed powder. S4.2 The thoroughly ground mixed powder is sintered at high temperature using a segmented heating method. After sintering, it is naturally cooled to room temperature to obtain the sintered active material. S4.3. The sintered active material is ultrasonically treated at 300~500W for 1~2h, centrifuged, cleaned, and dried in a vacuum environment at 80~100℃ for 68~12h to obtain single crystal NCM523 cathode material, thus realizing material regeneration.

[0038] In this invention, electrolytic treatment and low-voltage pulse stripping can be performed under controlled potential and treatment time to ensure the stability of the cathode material's crystal structure and to achieve complete removal of surface residues and pre-lithiation. Single-crystal sintering conditions can be optimized as needed, including sintering temperature, time, and reaction atmosphere, to further improve the material's electrochemical performance and cycle stability.

[0039] In a second aspect, the present invention provides a single-crystal NCM523 cathode material obtained by the above-described recycling method; the material has a complete crystal structure, few surface residues, and high specific capacity, excellent cycle performance and rate performance.

[0040] In a third aspect, the present invention provides a lithium-ion battery comprising a single-crystal NCM523 cathode material obtained by the above-described recycling method. This battery exhibits high cycle performance, excellent rate performance, and good structural stability, and is suitable for applications such as new energy vehicles, energy storage systems, and portable electronic devices.

[0041] The battery also includes an electrolyte and a separator suitable for lithium ions. The electrolyte may be a carbonate solution containing lithium salts, and the separator may be a polypropylene membrane, a polyethylene membrane, a composite membrane, or a cellulose nonwoven membrane.

[0042] Batteries using the recycled materials of this invention can significantly improve battery capacity, extend cycle life, and have high energy density and safety.

[0043] In this invention, the vacuum drying temperature is 80~100℃, for example, it can be 100℃, 102℃, 104℃, 106℃, 108℃, 110℃, 115℃, 120℃, but is not limited thereto; the drying time is 8~10h, for example, it can be 8h, 9h, 10h, but is not limited thereto.

[0044] In this invention, the high-temperature sintering is performed in stages: under an oxygen atmosphere, the temperature is first held at 300°C for 1.5 to 2.5 hours, then at 600°C for 3.5 to 4.5 hours, and finally at 900 to 970°C for 10 to 18 hours. Typical but non-limiting temperature conditions for the final high-temperature sintering temperature of 900 to 970°C include 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, and 970°C; typical but non-limiting time conditions for the high-temperature sintering include 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, and 18 hours.

[0045] In this invention, the concentration of the lithium sulfate solution is 1~2 mol / L, for example, 1 mol / L, 1.25 mol / L, 1.5 mol / L, 1.75 mol / L, or 2 mol / L.

[0046] In this invention, lithium source molten salt is added with an excess coefficient of 5-15%, that is, the corresponding lithium source molten salt is weighed out according to the ratio of lithium element to target product stoichiometry of 5-15%.

[0047] In a preferred embodiment, the disassembled retired NCM523 cathode material is obtained by discharging a waste NCM523 pouch battery to 1.1V, repeating the discharge 3-4 times to ensure voltage stability after discharge, and then disassembling the battery in a fume hood.

[0048] In a preferred embodiment, the low-voltage pulse stripping method is used under the following conditions, but not limitingly: the voltage is 20V, the power-on time is 2s, the power-off time is 4s, and the cycle is repeated twice.

[0049] In this invention, the electrolysis potential can be -1.2V, -1.25V, -1.3V, -1.35V and -1.4V respectively, to achieve pre-lithiation of the positive electrode and expand the grain boundary gap.

[0050] In a preferred embodiment, the mass ratio of lithium nitrate, lithium hydroxide monohydrate, and lithium carbonate is, but not limited to, 3:2:(0.3~1).

[0051] In a preferred embodiment, the alcohol solvent includes, but is not limited to, at least one of methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, isobutanol, sec-butanol, tert-butanol, n-pentanol, sec-pentanol, n-octanol, sec-octanol, and n-hexanol.

[0052] The present invention will be further illustrated below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.

[0053] Example 1 The electrochemical pretreatment and subsequent polycrystalline transformation of waste NCM523 cathode material for single-crystal recycling method includes the following steps: S1. Preprocessing: S1.1 Discharge the waste NCM523 soft pack battery to 1.1V, repeat the discharge 3~4 times to ensure the voltage is stable after discharge, then disassemble the battery in a fume hood to obtain the disassembled retired NCM523 positive electrode material, and put the disassembled retired NCM523 positive electrode material into a vacuum oven at 80℃ for 12h. S1.2. Then, use DMC to immerse the dried NCM523 cathode material to thoroughly clean the residual electrolyte on the surface of the cathode material. Finally, use anhydrous ethanol to clean the surface of the cathode material again, and put it into a vacuum oven at 80°C for 12 hours to dry it again, so as to obtain the pretreated NCM523 cathode material. S2, Electrolytic pre-lithiation treatment: The pretreated NCM523 cathode material is cut into 3cm pieces. 2 ×3cm 2The electrode was then subjected to constant potential electrochemical pre-lithiation treatment: a three-electrode electrochemical system was used, with a silver chloride electrode as the reference electrode, a platinum electrode as the counter electrode, and the pretreated NCM523 cathode material as the working electrode. The electrolyte was a 2 mol / L lithium sulfate solution. Electrolysis was carried out at a potential of -1.35V for 3 hours. The surface was then thoroughly cleaned with deionized water to remove residual lithium sulfate solution. Finally, the electrode was cleaned with ethanol and dried in a vacuum oven at 80℃ for 6 hours to obtain the pre-lithiated NCM523 cathode material. S3. Stripping: The pre-lithiated NCM523 cathode material after electrolysis is separated from the current collector using a low-voltage pulse stripping method. A dual-electrode system is used: the positive electrode is the pre-lithiated NCM523 cathode material after electrolysis, and the negative electrode is a platinum electrode. The electrolyte is a 1 mol / L lithium sulfate solution. A 20V voltage is applied for 2 seconds, then de-energized for 4 seconds, and this cycle is repeated twice to completely strip the active material from the current collector. The surface is then thoroughly cleaned with deionized water to remove residual lithium sulfate solution, and finally cleaned with ethanol. After drying in a vacuum oven at 80℃ for 6 hours, the stripped active material LiNi is obtained. 0.5 Co 0.2 Mn 0.3 O2, which is the stripped NCM523 cathode material; S4, High-temperature sintering: S4.1, the stripped active material LiNi 0.5 Co 0.2 Mn 0.3 O2 is ground into powder, then thoroughly ground with lithium source molten salt, mixed evenly, and lithium source molten salt is added in excess at a rate of 10%. The lithium source molten salt is composed of lithium nitrate, lithium hydroxide monohydrate and lithium carbonate in a mass ratio of 3:2:0.5 to obtain a mixed powder. S4.2. Place the thoroughly ground mixed powder into a crucible, spread it evenly, and place it in a tube furnace purged with oxygen. Perform high-temperature sintering using a segmented heating method: first, hold at 300℃ for 2 hours, then at 600℃ for 3 hours, and finally at 950℃ for 15 hours. After sintering, allow it to cool naturally to room temperature to obtain the sintered active material LiNi. 0.5 Co 0.2 Mn 0.3 O2 powder; S4.3, sinter the active material LiNi 0.5 Co 0.2 Mn 0.3 O2 powder was ultrasonically treated at 300~500W for 1 hour, then centrifuged 5 times, discarding the supernatant each time; then washed 5 times with deionized water, and finally washed once with ethanol. The powder was then placed in a vacuum oven and dried at 80℃ for 12 hours to obtain single-crystal NCM523 cathode material.

[0054] Example 2 The electrochemical pretreatment and subsequent polycrystalline transformation of waste NCM523 cathode material for single-crystal recycling method includes the following steps: S1. Preprocessing: S1.1 Discharge the waste NCM523 soft pack battery to 1.1V, repeat the discharge 3~4 times to ensure the voltage is stable after discharge, then disassemble the battery in a fume hood to obtain the disassembled retired NCM523 positive electrode material, and put the disassembled retired NCM523 positive electrode material into a vacuum oven at 90℃ for 10h. S1.2. Then, use DMC to immerse the dried NCM523 cathode material to thoroughly clean the residual electrolyte on the surface of the cathode material. Finally, use anhydrous ethanol to clean the surface of the cathode material again, and put it into a vacuum oven at 90°C for 10 hours to dry it again, so as to obtain the pretreated NCM523 cathode material. S2, Electrolytic pre-lithiation treatment: The pretreated NCM523 cathode material is cut into 3cm pieces. 2 ×3cm 2 The electrode was then subjected to constant potential electrochemical pre-lithiation treatment: a three-electrode electrochemical system was used, with a silver chloride electrode as the reference electrode, a platinum electrode as the counter electrode, and the pretreated NCM523 cathode material as the working electrode. The electrolyte was a 1 mol / L lithium sulfate solution. Electrolysis was carried out at a potential of -1.3V for 3 hours. The surface was then thoroughly cleaned with deionized water to remove residual lithium sulfate solution. Finally, the electrode was cleaned with ethanol and dried in a vacuum oven at 80℃ for 6 hours to obtain the pre-lithiated NCM523 cathode material. S3. Stripping: The pre-lithiated NCM523 cathode material after electrolysis is separated from the current collector using a low-voltage pulse stripping method. A dual-electrode system is used: the positive electrode is the pre-lithiated NCM523 cathode material after electrolysis, and the negative electrode is a platinum electrode. The electrolyte is a 1 mol / L lithium sulfate solution. A 20V voltage is applied for 2 seconds, then de-energized for 4 seconds, and this cycle is repeated twice to completely strip the active material from the current collector. The surface is then thoroughly cleaned with deionized water to remove residual lithium sulfate solution, and finally cleaned with ethanol. After drying in a vacuum oven at 80℃ for 6 hours, the stripped active material LiNi is obtained. 0.5 Co 0.2 Mn 0.3 O2, which is the stripped NCM523 cathode material; S4, High-temperature sintering: S4.1, the stripped active material LiNi 0.5 Co 0.2 Mn 0.3 O2 is ground into powder, then thoroughly ground with lithium source molten salt, mixed evenly, and lithium source molten salt is added in excess at a rate of 10%. The lithium source molten salt is composed of lithium nitrate, lithium hydroxide monohydrate and lithium carbonate in a mass ratio of 3:2:1 to obtain a mixed powder. S4.2. Place the thoroughly ground mixed powder into a crucible, spread it evenly, and place it in a tube furnace purged with oxygen. Perform high-temperature sintering using a segmented heating method: first, hold at 300℃ for 2 hours, then at 600℃ for 3 hours, and finally at 950℃ for 15 hours. After sintering, allow it to cool naturally to room temperature to obtain the sintered active material LiNi. 0.5 Co 0.2 Mn 0.3 O2 powder; S4.3, sinter the active material LiNi 0.5 Co 0.2 Mn 0.3 O2 powder was ultrasonically treated at 300~500W for 1 hour, then centrifuged 5 times, discarding the supernatant each time; then washed 5 times with deionized water, and finally washed once with ethanol. The powder was then placed in a vacuum oven and dried at 80℃ for 12 hours to obtain single-crystal NCM523 cathode material.

[0055] Example 3 The electrochemical pretreatment and subsequent polycrystalline transformation of waste NCM523 cathode material for single-crystal recycling method includes the following steps: S1. Preprocessing: S1.1 Discharge the waste NCM523 soft pack battery to 1.1V, repeat the discharge 3~4 times to ensure the voltage is stable after discharge, then disassemble the battery in a fume hood to obtain the disassembled retired NCM523 positive electrode material, and put the disassembled retired NCM523 positive electrode material into a vacuum oven at 100℃ for 8 hours. S1.2. Then, use DMC to immerse the dried NCM523 cathode material to thoroughly clean the residual electrolyte on the surface of the cathode material. Finally, use anhydrous ethanol to clean the surface of the cathode material again, and put it into a vacuum oven at 100°C for 8 hours to obtain the pretreated NCM523 cathode material. S2, Electrolytic pre-lithiation treatment: The pretreated NCM523 cathode material is cut into 3cm pieces. 2 ×3cm 2 The electrode was then subjected to constant potential electrochemical pre-lithiation treatment: a three-electrode electrochemical system was used, with a silver chloride electrode as the reference electrode, a platinum electrode as the counter electrode, and the pretreated NCM523 cathode material as the working electrode. The electrolyte was a 1 mol / L lithium sulfate solution. Electrolysis was carried out at a potential of -1.25V for 3 hours. The surface was then thoroughly cleaned with deionized water to remove residual lithium sulfate solution. Finally, the surface was cleaned with ethanol and dried in a vacuum oven at 100℃ for 6 hours to obtain the pre-lithiated NCM523 cathode material. S3. Stripping: The pre-lithiated NCM523 cathode material after electrolysis is separated from the current collector using a low-voltage pulse stripping method. A dual-electrode system is used: the positive electrode is the pre-lithiated NCM523 cathode material after electrolysis, and the negative electrode is a platinum electrode. The electrolyte is a 1 mol / L lithium sulfate solution. A 20V voltage is applied for 2 seconds, then de-energized for 4 seconds, and this cycle is repeated twice to completely strip the active material from the current collector. The surface is then thoroughly cleaned with deionized water to remove residual lithium sulfate solution, and finally cleaned with ethanol. After drying in a vacuum oven at 100℃ for 6 hours, the stripped active material LiNi is obtained. 0.5 Co 0.2 Mn 0.3 O2, which is the stripped NCM523 cathode material; S4, High-temperature sintering: S4.1, the stripped active material LiNi 0.5 Co 0.2 Mn 0.3 O2 is ground into powder, then thoroughly ground with lithium source molten salt, mixed evenly, and lithium source molten salt is added in excess at a rate of 10%. The lithium source molten salt is composed of lithium nitrate, lithium hydroxide monohydrate and lithium carbonate in a mass ratio of 3:2:0.3 to obtain a mixed powder. S4.2. Place the thoroughly ground mixed powder into a crucible, spread it evenly, and place it in a tube furnace purged with oxygen. Perform high-temperature sintering using a segmented heating method: first, hold at 300℃ for 2 hours, then at 600℃ for 3 hours, and finally at 950℃ for 15 hours. After sintering, allow it to cool naturally to room temperature to obtain the sintered active material LiNi. 0.5 Co 0.2 Mn 0.3 O2 powder; S4.3, sinter the active material LiNi 0.5 Co 0.2 Mn 0.3 O2 powder was ultrasonically treated at 300~500W for 1 hour, then centrifuged 5 times, discarding the supernatant each time; then washed 5 times with deionized water, and finally washed once with ethanol. The powder was then placed in a vacuum oven and dried at 80℃ for 12 hours to obtain single-crystal NCM523 cathode material.

[0056] Example 4 The electrochemical pretreatment and subsequent polycrystalline transformation of waste NCM523 cathode material for single-crystal recycling method includes the following steps: S1. Preprocessing: S1.1 Discharge the waste NCM523 soft pack battery to 1.1V, repeat the discharge 3~4 times to ensure the voltage is stable after discharge, then disassemble the battery in a fume hood to obtain the disassembled retired NCM523 positive electrode material, and put the disassembled retired NCM523 positive electrode material into a vacuum oven at 90℃ for 10h. S1.2. Then, use DMC to immerse the dried NCM523 cathode material to thoroughly clean the residual electrolyte on the surface of the cathode material. Finally, use anhydrous ethanol to clean the surface of the cathode material again, and put it into a vacuum oven at 90°C for 10 hours to dry it again, so as to obtain the pretreated NCM523 cathode material. S2, Electrolytic pre-lithiation treatment: The pretreated NCM523 cathode material is cut into 3cm pieces. 2 ×3cm 2 The electrode was then subjected to constant potential electrochemical pre-lithiation treatment: a three-electrode electrochemical system was used, with a silver chloride electrode as the reference electrode, a platinum electrode as the counter electrode, and the pretreated NCM523 cathode material as the working electrode. The electrolyte was a 1.5 mol / L lithium sulfate solution. Electrolysis was carried out at a potential of -1.4 V for 4 h. The surface was then thoroughly cleaned with deionized water to remove residual lithium sulfate solution. Finally, the surface was cleaned with ethanol and dried in a vacuum oven at 90 °C for 8 h to obtain the pre-lithiated NCM523 cathode material. S3. Stripping: The pre-lithiated NCM523 cathode material is separated from the current collector using a low-voltage pulse stripping method. A dual-electrode system is used: the positive electrode is the pre-lithiated NCM523 cathode material, and the negative electrode is a platinum electrode. The electrolyte is a 1.5 mol / L lithium sulfate solution. A 15V voltage is applied for 3 seconds, then de-energized for 5 seconds, and this cycle is repeated 3 times to completely strip the active material from the current collector. The surface is then thoroughly cleaned with deionized water to remove residual lithium sulfate solution, and finally cleaned with ethanol. After drying in a vacuum oven at 100℃ for 6 hours, the stripped active material LiNi is obtained. 0.5 Co 0.2 Mn 0.3 O2, which is the stripped NCM523 cathode material; S4, High-temperature sintering: S4.1, the stripped active material LiNi 0.5 Co 0.2 Mn 0.3 O2 is ground into powder, then thoroughly ground with lithium source molten salt, mixed evenly, and lithium source molten salt is added in excess at a rate of 5%. The lithium source molten salt is composed of lithium nitrate, lithium hydroxide monohydrate and lithium carbonate in a mass ratio of 3:2:0.8 to obtain a mixed powder. S4.2. Place the thoroughly ground mixed powder into a crucible, spread it evenly, and place it in a tube furnace purged with oxygen. Perform high-temperature sintering using a segmented heating method: first, hold at 300℃ for 1.5 hours, then at 600℃ for 2.5 hours, and finally at 920℃ for 18 hours. After sintering, allow it to cool naturally to room temperature to obtain the sintered active material LiNi. 0.5 Co 0.2 Mn 0.3 O2 powder; S4.3, sinter the active material LiNi 0.5 Co 0.2 Mn 0.3 O2 powder was ultrasonically treated at 300~500W for 1 hour, then centrifuged 5 times, discarding the supernatant each time; then washed 5 times with deionized water, and finally washed once with ethanol. The powder was then placed in a vacuum oven and dried at 100℃ for 10 hours to obtain single-crystal NCM523 cathode material.

[0057] Example 5 The electrochemical pretreatment and subsequent polycrystalline transformation of waste NCM523 cathode material for single-crystal recycling method includes the following steps: S1. Preprocessing: S1.1 Discharge the waste NCM523 soft pack battery to 1.1V, repeat the discharge 3~4 times to ensure the voltage is stable after discharge, then disassemble the battery in a fume hood to obtain the disassembled retired NCM523 positive electrode material, and put the disassembled retired NCM523 positive electrode material into a vacuum oven at 90℃ for 10h. S1.2. Then, use DMC to immerse the dried NCM523 cathode material to thoroughly clean the residual electrolyte on the surface of the cathode material. Finally, use anhydrous ethanol to clean the surface of the cathode material again, and put it into a vacuum oven at 90°C for 10 hours to dry it again, so as to obtain the pretreated NCM523 cathode material. S2, Electrolytic pre-lithiation treatment: The pretreated NCM523 cathode material is cut into 3cm pieces. 2 ×3cm 2 The electrode was then subjected to constant potential electrochemical pre-lithiation treatment: a three-electrode electrochemical system was used, with a silver chloride electrode as the reference electrode, a platinum electrode as the counter electrode, and the pretreated NCM523 cathode material as the working electrode. The electrolyte was a 1.75 mol / L lithium sulfate solution. Electrolysis was carried out at a potential of -1.2 V for 2 h. The surface was then thoroughly cleaned with deionized water to remove residual lithium sulfate solution. Finally, the electrode was cleaned with ethanol and dried in a vacuum oven at 90 °C for 8 h to obtain the pre-lithiated NCM523 cathode material. S3. Stripping: The pre-lithiated NCM523 cathode material after electrolysis is separated from the current collector using a low-voltage pulse stripping method. A dual-electrode system is used: the positive electrode is the pre-lithiated NCM523 cathode material after electrolysis, and the negative electrode is a platinum electrode. The electrolyte is a 2 mol / L lithium sulfate solution. A 25V voltage is applied, and the voltage is turned off for 3 seconds, repeating this cycle once to completely strip the active material from the current collector. The surface is then thoroughly cleaned with deionized water to remove residual lithium sulfate solution, and finally cleaned with ethanol. After drying in a vacuum oven at 90℃ for 8 hours, the stripped active material LiNi is obtained. 0.5 Co 0.2 Mn 0.3 O2, which is the stripped NCM523 cathode material; S4, High-temperature sintering: S4.1, the stripped active material LiNi 0.5 Co 0.2 Mn 0.3 O2 is ground into powder, then thoroughly ground with lithium source molten salt, mixed evenly, and lithium source molten salt is added in excess at a rate of 5%. The lithium source molten salt is composed of lithium nitrate, lithium hydroxide monohydrate and lithium carbonate in a mass ratio of 3:2:0.8 to obtain a mixed powder. S4.2. Place the thoroughly ground mixed powder into a crucible, spread it evenly, and place it in a tube furnace purged with oxygen. Perform high-temperature sintering using a segmented heating method: first, hold at 300℃ for 2.5 hours, then at 600℃ for 3.5 hours, and finally at 970℃ for 10 hours. After sintering, allow it to cool naturally to room temperature to obtain the sintered active material LiNi. 0.5 Co 0.2 Mn 0.3 O2 powder; S4.3, sinter the active material LiNi 0.5 Co 0.2 Mn 0.3 O2 powder was ultrasonically treated at 300~500W for 1 hour, then centrifuged 5 times, discarding the supernatant each time; then washed 5 times with deionized water, and finally washed once with ethanol. The powder was then placed in a vacuum oven at 90℃ and dried for 10 hours to obtain single-crystal NCM523 cathode material.

[0058] Comparative Example 1 The recycling method for waste NCM523 cathode material includes the following steps: S1. Preprocessing: S1.1 Discharge the waste NCM523 soft pack battery to 1.1V, repeat the discharge 3~4 times to ensure the voltage is stable after discharge, then disassemble the battery in a fume hood to obtain the disassembled retired NCM523 positive electrode material, and put the disassembled retired NCM523 positive electrode material into a vacuum oven at 80℃ for 12h. S1.2. Then, use DMC to immerse the dried NCM523 cathode material to thoroughly clean the residual electrolyte on the surface of the cathode material. Finally, use anhydrous ethanol to clean the surface of the cathode material again, and put it into a vacuum oven at 80°C for 12 hours to dry it again, so as to obtain the pretreated NCM523 cathode material. S2. Stripping: Cut the pretreated NCM523 cathode material into 3cm pieces. 2 ×3cm 2 The electrode was prepared by using a traditional mechanical peeling method to scrape the active material off the surface of the electrode, and then drying it in a vacuum oven at 80°C for 6 hours to obtain the peeled active material LiNi. 0.5 Co 0.2 Mn 0.3 O2, which is the stripped NCM523 cathode material; S3, the stripped active material LiNi 0.5 Co 0.2 Mn 0.3 O2 is ground into powder to obtain the recycled NCM523 cathode material.

[0059] Comparative Example 1 uses mechanical stripping instead of low-pressure pulse stripping and does not include constant potential electrochemical pre-lithiation treatment, high-temperature sintering steps with segmented heating, or lithium source molten salt.

[0060] Comparative Example 2 The electrochemical pretreatment and subsequent polycrystalline transformation of waste NCM523 cathode material for single-crystal recycling method includes the following steps: S1. Preprocessing: S1.1 Discharge the waste NCM523 soft pack battery to 1.1V, repeat the discharge 3~4 times to ensure the voltage is stable after discharge, then disassemble the battery in a fume hood to obtain the disassembled retired NCM523 positive electrode material, and put the disassembled retired NCM523 positive electrode material into a vacuum oven at 80℃ for 12h. S1.2. Then, use DMC to immerse the dried NCM523 cathode material to thoroughly clean the residual electrolyte on the surface of the cathode material. Finally, use anhydrous ethanol to clean the surface of the cathode material again, and put it into a vacuum oven at 80°C for 12 hours to dry it again, so as to obtain the pretreated NCM523 cathode material. S2. Stripping: Cut the pretreated NCM523 cathode material into 3cm pieces. 2 ×3cm 2The active material was separated from the current collector using a low-voltage pulse stripping method. A dual-electrode system was used: the positive electrode was pre-lithiated NCM523 cathode material, and the negative electrode was a platinum electrode. The electrolyte was a 1 mol / L lithium sulfate solution. A voltage of 20V was applied for 2 seconds, then de-energized for 4 seconds, for two cycles. This completely stripped the active material from the current collector. The surface was then thoroughly cleaned with deionized water to remove residual lithium sulfate solution, and finally cleaned with ethanol. The material was then dried in a vacuum oven at 80℃ for 6 hours to obtain the stripped active material, LiNi. 0.5 Co 0.2 Mn 0.3 O2, which is the stripped NCM523 cathode material; S3, the stripped active material LiNi 0.5 Co 0.2 Mn 0.3 O2 is ground into powder to obtain the recycled NCM523 cathode material.

[0061] Comparative Example 2 does not contain constant potential electrochemical pre-lithiation treatment, high-temperature sintering steps with segmented heating, or lithium source molten salt.

[0062] Comparative Example 3 The electrochemical pretreatment and subsequent polycrystalline transformation of waste NCM523 cathode material for single-crystal recycling method includes the following steps: S1. Preprocessing: S1.1 Discharge the waste NCM523 soft pack battery to 1.1V, repeat the discharge 3~4 times to ensure the voltage is stable after discharge, then disassemble the battery in a fume hood to obtain the disassembled retired NCM523 positive electrode material, and put the disassembled retired NCM523 positive electrode material into a vacuum oven at 90℃ for 10h. S1.2. Then, use DMC to immerse the dried NCM523 cathode material to thoroughly clean the residual electrolyte on the surface of the cathode material. Finally, use anhydrous ethanol to clean the surface of the cathode material again, and put it into a vacuum oven at 90°C for 10 hours to dry it again, so as to obtain the pretreated NCM523 cathode material. S2. Stripping: Cut the pretreated NCM523 cathode material into 3cm pieces. 2 ×3cm 2 The active material was separated from the current collector using a low-voltage pulse stripping method. A dual-electrode system was used: the positive electrode was pre-lithiated NCM523 cathode material, and the negative electrode was a platinum electrode. The electrolyte was a 1 mol / L lithium sulfate solution. A voltage of 20V was applied for 2 seconds, then de-energized for 4 seconds, for two cycles. This completely stripped the active material from the current collector. The surface was then thoroughly cleaned with deionized water to remove residual lithium sulfate solution, and finally cleaned with ethanol. The material was then dried in a vacuum oven at 80℃ for 6 hours to obtain the stripped active material, LiNi.0.5 Co 0.2 Mn 0.3 O2, which is the stripped NCM523 cathode material; S3, High-temperature sintering: S3.1, the stripped active material LiNi 0.5 Co 0.2 Mn 0.3 O2 is ground into powder, then thoroughly ground with lithium source molten salt, mixed evenly, and lithium source molten salt is added in excess at a rate of 10%. The lithium source molten salt is composed of lithium nitrate, lithium hydroxide monohydrate and lithium carbonate in a mass ratio of 3:2:1 to obtain a mixed powder. S3.2. Place the thoroughly ground mixed powder into a crucible, spread it evenly, and place it in a tube furnace purged with oxygen. Perform high-temperature sintering using a segmented heating method: first, hold at 300℃ for 2 hours, then at 600℃ for 3 hours, and finally at 950℃ for 15 hours. After sintering, allow it to cool naturally to room temperature to obtain the sintered active material LiNi. 0.5 Co 0.2 Mn 0.3 O2 powder; S3.3, sinter the active material LiNi 0.5 Co 0.2 Mn 0.3 O2 powder was ultrasonically treated at 300~500W for 1 hour, then centrifuged 5 times, discarding the supernatant each time; then washed 5 times with deionized water, and finally washed once with ethanol. The powder was then placed in a vacuum oven and dried at 80℃ for 12 hours to obtain single-crystal NCM523 cathode material.

[0063] Comparative Example 3 does not contain potentiostatic electrochemical pre-lithiation treatment.

[0064] Comparative Example 4 The electrochemical pretreatment and subsequent polycrystalline transformation of waste NCM523 cathode material for single-crystal recycling method includes the following steps: S1. Preprocessing: S1.1 Discharge the waste NCM523 soft pack battery to 1.1V, repeat the discharge 3~4 times to ensure the voltage is stable after discharge, then disassemble the battery in a fume hood to obtain the disassembled retired NCM523 positive electrode material, and put the disassembled retired NCM523 positive electrode material into a vacuum oven at 90℃ for 10h. S1.2. Then, use DMC to immerse the dried NCM523 cathode material to thoroughly clean the residual electrolyte on the surface of the cathode material. Finally, use anhydrous ethanol to clean the surface of the cathode material again, and put it into a vacuum oven at 90°C for 10 hours to dry it again, so as to obtain the pretreated NCM523 cathode material. S2, Electrolytic pre-lithiation treatment: The pretreated NCM523 cathode material is cut into 3cm pieces. 2 ×3cm 2 The electrode was then subjected to constant potential electrochemical pre-lithiation treatment: a three-electrode electrochemical system was used, with a silver chloride electrode as the reference electrode, a platinum electrode as the counter electrode, and the pretreated NCM523 cathode material as the working electrode. The electrolyte was a 1 mol / L lithium sulfate solution. Electrolysis was carried out at a potential of -1.3V for 3 hours. The surface was then thoroughly cleaned with deionized water to remove residual lithium sulfate solution. Finally, the surface was cleaned with ethanol and dried in a vacuum oven at 80℃ for 6 hours to obtain the pre-lithiated NCM523 cathode material. S3. Stripping: The pre-lithiated NCM523 cathode material is separated from the current collector using a low-voltage pulse stripping method. A dual-electrode system is used: the positive electrode is the pre-lithiated NCM523 cathode material, the negative electrode is a platinum electrode, and the electrolyte is a 1 mol / L lithium sulfate solution. A voltage of 20V is applied for 2 seconds, then de-energized for 4 seconds, for two cycles. This completely strips the active material from the current collector. The surface is then thoroughly cleaned with deionized water to remove residual lithium sulfate solution, and finally cleaned with ethanol. After drying in a vacuum oven at 80℃ for 6 hours, the stripped active material LiNi is obtained. 0.5 Co 0.2 Mn 0.3 O2, which is the stripped NCM523 cathode material; S4, High-temperature sintering: S4.1, the stripped active material LiNi 0.5 Co 0.2 Mn 0.3 O2 is ground into powder, then thoroughly ground with lithium source molten salt, mixed evenly, and lithium source molten salt is added in excess at a rate of 10%. The lithium source molten salt is lithium carbonate, and a mixed powder is obtained. S4.2. Place the thoroughly ground mixed powder into a crucible, spread it evenly, and place it in a tube furnace with oxygen supply. Perform high-temperature sintering using a constant temperature method: hold at 850℃ for 20 hours. After sintering, allow it to cool naturally to room temperature to obtain the sintered active material LiNi. 0.5 Co 0.2 Mn 0.3 O2 powder; S4.3, sinter the active material LiNi 0.5 Co 0.2 Mn 0.3 O2 powder was ultrasonically treated at 300~500W for 1 hour, then centrifuged 5 times, discarding the supernatant each time; then washed 5 times with deionized water, and finally washed once with ethanol. The powder was then placed in a vacuum oven and dried at 80℃ for 12 hours to obtain single-crystal NCM523 cathode material.

[0065] Comparative Example 4 was sintered at high temperature using a constant temperature method, with lithium carbonate as the lithium source molten salt.

[0066] Comparative Example 5 The electrochemical pretreatment and subsequent polycrystalline transformation of waste NCM523 cathode material for single-crystal recycling method includes the following steps: S1. Preprocessing: S1.1 Discharge the waste NCM523 soft pack battery to 1.1V, repeat the discharge 3~4 times to ensure the voltage is stable after discharge, then disassemble the battery in a fume hood to obtain the disassembled retired NCM523 positive electrode material, and put the disassembled retired NCM523 positive electrode material into a vacuum oven at 90℃ for 10h. S1.2. Then, use DMC to immerse the dried NCM523 cathode material to thoroughly clean the residual electrolyte on the surface of the cathode material. Finally, use anhydrous ethanol to clean the surface of the cathode material again, and put it into a vacuum oven at 90°C for 10 hours to dry it again, so as to obtain the pretreated NCM523 cathode material. S2, Electrolytic pre-lithiation treatment: The pretreated NCM523 cathode material is cut into 3cm pieces. 2 ×3cm 2 The electrode was then subjected to constant potential electrochemical pre-lithiation treatment: a three-electrode electrochemical system was used, with a silver chloride electrode as the reference electrode, a platinum electrode as the counter electrode, and the pretreated NCM523 cathode material as the working electrode. The electrolyte was a 1 mol / L lithium sulfate solution. Electrolysis was carried out at a potential of -1.3V for 3 hours. The surface was then thoroughly cleaned with deionized water to remove residual lithium sulfate solution. Finally, the surface was cleaned with ethanol and dried in a vacuum oven at 80℃ for 6 hours to obtain the pre-lithiated NCM523 cathode material. S3. Stripping: The pre-lithiated NCM523 cathode material is separated from the current collector using a low-voltage pulse stripping method. A dual-electrode system is used: the positive electrode is the pre-lithiated NCM523 cathode material, the negative electrode is a platinum electrode, and the electrolyte is a 1 mol / L lithium sulfate solution. A voltage of 20V is applied for 2 seconds, then de-energized for 4 seconds, for two cycles. This completely strips the active material from the current collector. The surface is then thoroughly cleaned with deionized water to remove residual lithium sulfate solution, and finally cleaned with ethanol. After drying in a vacuum oven at 80℃ for 6 hours, the stripped active material LiNi is obtained. 0.5 Co 0.2 Mn 0.3 O2, which is the stripped NCM523 cathode material; S4. The stripped active material LiNi 0.5 Co 0.2 Mn 0.3 O2 is ground into powder to obtain the recycled NCM523 cathode material.

[0067] Comparative Example 5 does not contain a high-temperature sintering step with segmented heating and does not add lithium source molten salt.

[0068] Test case Test Example 1: XRD analysis was performed on waste NCM523 cathode material, NCM523 cathode material pre-lithiated by electrolysis at different potentials and electrolysis times in Examples 1-5, NCM523 cathode material after low-voltage pulse stripping obtained in Example 1, single-crystal NCM523 cathode material obtained in Example 1, and NCM523 cathode material after conventional mechanical stripping obtained in Comparative Example 1. The test results are as follows: Figures 1-5 and Figure 7 As shown.

[0069] pass Figures 1-5 and Figure 7 The XRD patterns of the waste NCM523 cathode material, after constant potential electrochemical pre-lithiation treatment and low-voltage pulse stripping, show a shift in the 003 peak and an expansion of the grain boundaries. This indicates that the constant potential electrochemical pre-lithiation treatment and low-voltage pulse stripping activate the grain boundaries within the waste polycrystalline NCM523 particles. Figure 5 The study found that the low-pressure pulse stripping method, compared to the traditional mechanical stripping method, more easily widens the grain boundaries of the material, which is beneficial for activating the grain boundaries inside waste polycrystalline NCM523 particles. During the constant potential electrochemical pre-intercalation lithium treatment, the re-intercalation of lithium ions and local electrochemical reactions cause lattice parameter adjustment, local stress release, and weakening of the bonding force between primary particles. The originally relatively tight grain boundary regions inside the polycrystalline secondary particles are widened to a certain extent, forming more open grain boundary interstices and ion transport channels. This grain boundary widening effect is conducive to the diffusion of lithium source and molten salt medium into the particle interior during the subsequent molten salt treatment, promoting lithium replenishment inside the particles, grain boundary migration, and grain melting. The reconstructed layered structure improves the efficiency of converting waste cathode materials into recycled materials with low grain boundary density and high crystallinity. During the low-voltage pulse treatment, the waste NCM523 cathode material is subjected to the combined effects of the pulsed electric field and electrochemical reactions in the lithium sulfate electrolyte. On the one hand, the electric field promotes the migration and embedding of lithium ions into the layered structure of the waste NCM523, thus compensating for the lithium loss in the crystal structure after long-term cycling. On the other hand, the pulsed electric field generates local electrochemical reactions and gas evolution at the interface between the cathode material particles, binder, and aluminum foil current collector, weakening the binding of the PVDF binder and aluminum foil interface to the active material. Figure 6 The stripping phenomenon shown after the low-voltage pulse stripping enables the positive electrode active material to be rapidly stripped from the current collector surface.

[0070] Test Example 2: SEM analysis was performed on the waste NCM523 cathode material and the single-crystal NCM523 cathode material obtained in Example 2. The results are as follows: Figure 10 and Figure 11 As shown.

[0071] from Figure 10 and Figure 11 It can be seen that the waste NCM523 cathode material ( Figure 10 Secondary particles, which are spherical and formed by the accumulation of primary particles, have cracks, pores, and flocculent deposits on their surface; the regenerated single-crystal NCM523 cathode material obtained in Example 2 ( Figure 11 The recycled single-crystal NCM523 cathode material exhibits independent primary particles with smooth surfaces, no cracks or impurities, and virtually no agglomeration, resulting in superior electrochemical performance.

[0072] Test Example 3: Using the NCM523 cathode materials prepared in Examples 1-5 and Comparative Examples 2-5, as well as waste NCM523 cathode materials, as cathodes, and 1M LiPF6 ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl carbonate (EMC) in a volume ratio of 1:1:1 as the electrolyte, and glass fiber as the separator, CR2025 coin cells were assembled. The battery cycle and rate performance were tested at 170 mA / g. The battery cycle performance results are shown in Table 1 and... Figure 5 As shown in Table 2, the rate performance is as follows: Figure 6 As shown.

[0073] Table 1 Cyclic Comparison Chart ; Table 2 Comparison Chart ; from Figure 8It was found that the capacity retention rate of Example 1 after 100 cycles at 1C was 5.24%, which far exceeded the performance of the waste NCM523 cathode material. Combined with the data in Table 1, the discharge specific capacity of the material obtained in Example 1 at 0.1C was 155.91 mAh / g, significantly higher than the 96.26 mAh / g of the material obtained by the low-voltage pulse stripping method only in Comparative Example 2. Furthermore, the capacity retention rate of Example 1 after 100 cycles at 0.1C was 68.9%, also significantly better than the 6.1% capacity retention rate of Comparative Example 2 after 100 cycles at 0.1C. This preliminarily confirms the improvement in cycle performance by the complete method. Further, although the 0.1C capacity of the material obtained by Comparative Example 3 without the constant-potential electrochemical pre-lithiation treatment was close to that of Example 1, the capacity retention rate of Comparative Example 3 after 100 cycles at 0.1C was only 5.5%, indicating a sudden collapse in high-rate capacity. This suggests that the constant-potential electrochemical pre-lithiation treatment step was missing. The material's structural defects were not repaired, making it unable to withstand high current impacts. Comparative Example 4 used lithium carbonate and constant temperature sintering at high temperature, resulting in a 0.1C capacity of only 102.34 mAh / g. After 100 cycles at 0.1C, the capacity retention rate was only 41.8%. Although the retention rate was relatively high, this was due to the extremely low intrinsic capacity of the active material, resulting in false cycle stability. Its full-rate capacity was far lower than that of Example 1. Comparative Example 5 lacked molten salt and segmented heating methods for high-temperature sintering. It only used constant potential electrochemical pre-intercalation combined with low-voltage pulse stripping. The resulting material had a 0.1C capacity of 135.4 mAh / g, which was somewhat recovered from the waste material, proving that the pretreatment was effective. However, according to Table 2, its high-rate capacity (e.g., only 5.29 mAh / g at 2C) was nearly 20 times lower than that of Example 1 (101.54 mAh / g at 2C), strongly demonstrating that the three-step synergy created a performance leap far greater than simple superposition.

[0074] Depend on Figure 9 The rate tests in Table 2 further confirmed the above conclusions. The discharge specific capacities of Example 1 at 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C were 163.69, 157.13, 142.73, 125.02, 101.54, and 59.68 mAh / g, respectively, which were significantly higher than those of Comparative Example 2 (102.94, 34.63, 7.5, 2.27, 1.01, and 0.52 mAh / g), indicating that the material obtained by the method of the present invention has excellent rate performance. Comparative Example 3 only had capacity at low rates, with a precipitous decline at high rates. Comparative Examples 4 and 5 lagged behind at all rates, further confirming that the individual and synergistic effects of pre-lithiation, pulse stripping, and specific molten salt sintering are indispensable.

[0075] In summary, this invention combines constant-potential electrochemical pre-lithiation with low-voltage pulse stripping for efficient pretreatment of waste NCM523 cathode materials. This is followed by lithium supplementation sintering using a specific molten salt system composed of lithium nitrate, lithium hydroxide monohydrate, and lithium carbonate, achieving a transformation from polycrystalline to monocrystalline. Comparative data confirms that these three elements functionally support each other and synergistically enhance each other's effects: pre-lithiation lays the foundation for structural repair and ion transport; pulse stripping maximizes the protection of precursor particle integrity; and the specific molten salt system facilitates the decisive monocrystalline transformation that leads to a significant performance leap. The superior cycling and high-rate performance resulting from this combination provides a new technical route for the high-value recycling of waste ternary cathode materials.

[0076] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit and essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0077] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for electrochemical pretreatment and subsequent polycrystalline transformation of waste NCM523 cathode material for single-crystal recycling, characterized in that, The recycling method steps are as follows: S1. Pretreatment: The disassembled retired NCM523 cathode material is pretreated by vacuum drying, solvent washing and vacuum drying again to obtain pretreated NCM523 cathode material. The solvent is dimethyl carbonate and alcohol solvent; S2. Electrolytic pre-lithiation treatment: The pretreated NCM523 cathode material is subjected to constant potential electrochemical pre-lithiation treatment in a three-electrode electrochemical system to obtain the electrolytically pre-lithiation-treated NCM523 cathode material. S3. Stripping: The active material of the pre-lithiated NCM523 cathode material after electrolysis is separated from the current collector by a low-voltage pulse stripping method, and then cleaned and dried to obtain the stripped active material, i.e., the stripped NCM523 cathode material. S4. High-temperature sintering: The stripped active material is ground into powder, then mixed evenly with lithium source molten salt through grinding, and then sintered at high temperature using a segmented heating method. After sintering, it is naturally cooled to room temperature, then subjected to ultrasonic treatment, centrifugal separation, cleaning, and vacuum drying to obtain single-crystal NCM523 cathode material.

2. The method for electrochemical pretreatment and subsequent polycrystalline to single-crystal recycling of waste NCM523 cathode material according to claim 1, characterized in that, In step S1, in the three-electrode electrochemical system, the reference electrode is a silver chloride electrode, the counter electrode is a platinum electrode, the working electrode is a pretreated NCM523 positive electrode material, and the electrolyte is a lithium sulfate solution.

3. The method for electrochemical pretreatment and subsequent polycrystalline to single-crystal recycling of waste NCM523 cathode material according to claim 1, characterized in that, In step S1, the conditions for the constant potential electrochemical pre-lithiation treatment are: electrolysis potential of -1.2 to -1.4V and electrolysis time of 1 to 3h.

4. The method for electrochemical pretreatment and subsequent polycrystalline to single-crystal recycling of waste NCM523 cathode material according to claim 1, characterized in that, The low-voltage pulse stripping method employs a dual-electrode system, with the positive electrode being the pre-lithiated NCM523 positive electrode material and the negative electrode being a platinum electrode. The electrolyte is a lithium sulfate solution.

5. The method for electrochemical pretreatment and subsequent polycrystalline to single-crystal recycling of waste NCM523 cathode material according to claim 1, characterized in that, In step S2, the conditions for the low-voltage pulse stripping method are: voltage of 15~25V, power-on time of 1~3s, power-off time of 3~5s, and 1~3 cycles.

6. The method for electrochemical pretreatment and subsequent polycrystalline to single-crystal recycling of waste NCM523 cathode material according to claim 1, characterized in that, In step S3, the amount of lithium source molten salt added is 5-15% excess; the lithium source molten salt is composed of lithium nitrate, lithium hydroxide monohydrate and lithium carbonate.

7. The method for electrochemical pretreatment and subsequent polycrystalline to single-crystal recycling of waste NCM523 cathode material according to claim 6, characterized in that, The mass ratio of lithium nitrate, lithium hydroxide monohydrate and lithium carbonate is 3:2:(0.3~1).

8. The method for electrochemical pretreatment and subsequent polycrystalline to single-crystal recycling of waste NCM523 cathode material according to claim 1, characterized in that, In step S3, the high-temperature sintering is carried out in stages: under an oxygen atmosphere, the temperature is first held at 300℃ for 1.5 to 2.5 hours, then at 600℃ for 3.5 to 4.5 hours, and finally at 900 to 970℃ for 10 to 18 hours.

9. A single-crystal NCM523 cathode material, characterized in that, The single-crystal NCM523 cathode material obtained by any one of the recycling methods of claims 1 to 9.

10. A lithium-ion battery, characterized in that, This includes single-crystal NCM523 cathode material obtained by the recycling method of any one of claims 9.